Of crabs and tall poppies: an exploratory study of attitudes and communicative behaviors toward women perceived as successful - Mancl, Anne C. (My University, 2006)
This exploratory, qualitative study will examine female attitudes and communication behaviors generated in response to women who are perceived as advantaged or "successful". The current study used the Tall Poppy Syndrome (TPS) as a framework for this investigation. Tall Poppy Syndrome, an Australian cultural expression, describes a "disease" that feeds on the notion that anyone who appears to represent high ability or admirable qualities (also known as 'tall poppies') must be attacked, demeaned, and brought down to the common level. Individuals with TPS, (known as "poppy clippers") believe others' perceived advantages to be an affront--an unbearable reminder of their own shortcomings (Peeters, 2004). This study investigates the characteristics of and underlying contributors to TPS within the context of American, Caucasian intrafemale relationships. Being a "tall poppy" or a "poppy clipper" could potentially cause women to experience relational conflict in social and organizational contexts leading to outcomes such as interpersonal clashing, indirect aggression, covert maliciousness, unfulfilled potential and organizational "brain drain." The research appears to indicate that a talented "tall poppy" is in a conundrum: if she is successful, she risks exclusion by her female peers. If she "plays small", she risks her own personal and professional fulfillment. This study examines a perplexing concern for many females: It sometimes appears that when talented, successful women try to flourish, there are frequently nearby females ready to pull them down. Does the successful, confident women feel "pulled down" or "clipped" by members of the "sisterhood" who see her as a threat? Are these talented women the target of other women's envy? What role might some women play in holding other women back? To gain insights on these questions and on the TPS phenomenon, focus group data from 40 adjust, Caucasian women in a Midwestern area was collected and analyzed using the grounded research methodology (Glaser & Straus, 1967). Using the Tall Poppy Syndrome construct, this study explains how woman respond and assign meaning to a perceived tall poppy, as well as how the 'tall poppy' responds to the envious rival. Generally finds focused on the perceived characteristics of tall poppies and poppy clippers, the negative communication behaviors poppy clipper use and finally, strategies the tall poppy uses in response to the poppy clipper. This research will add to the existing knowledge base on organizational, gender and interpersonal communication and may be a determining force in the effectiveness and stability of female relationships within society. With more information on this subject, organizations can provide awareness, open-dialogue opportunities, and appropriate training to minimize TPS's negative outcomes.
This file was viewed in Adobe Reader 7.0
Keywords: Women -- United States -- Psychology; Interpersonal conflict -- United States; Interpersonal relations -- United States; Women -- United States -- Attitudes